2000
DOI: 10.1177/156482650002100313
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Salt Fortified with Iron and Iodine on the Haemoglobin Levels and Productivity of Tea Pickers

Abstract: To determine if double-fortified salt improved the haemoglobin levels and productivity of tea pickers, a double-blind, randomized, placebo-controlled

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(42 citation statements)
references
References 6 publications
0
42
0
Order By: Relevance
“…The difference in change in hemoglobin ranged from 40 to 72 g/L (17) over 6 and 8 mo, respectively (16). To our knowledge, the present study is the first that describes the impact of DFS on iron-deficiency measures other than hemoglobin in women.…”
Section: Introductionmentioning
confidence: 99%
“…The difference in change in hemoglobin ranged from 40 to 72 g/L (17) over 6 and 8 mo, respectively (16). To our knowledge, the present study is the first that describes the impact of DFS on iron-deficiency measures other than hemoglobin in women.…”
Section: Introductionmentioning
confidence: 99%
“…As presented in Table 1, the most tested condiment, as a vehicle for efficacy or effectiveness of iron fortification, was salt. This fortification approach included 13 Double-fortified Salt (DFS) [21][22][23][24][25][26][27][28][29][30][31][32][33] and five Multiple Micronutrient Fortified Salt (MMFS) studies [34][35][36][37][38]. Only one study evaluated a seasoning powder [39], two studies evaluated fish sauce [40,41], and two studies evaluated soy sauce [42,43].…”
Section: Discussionmentioning
confidence: 99%
“…There were no efficacy or effectiveness studies of iron-fortified bouillon cubes. All studies were conducted in Asia or Africa using as subjects children or women of reproductive age during different time lengths using as fortificants a variety of iron forms that included micronized ground ferric pyrophosphate [21,30,33,38], encapsulated ferrous fumarate [21,31], ferrous fumarate [22], ferrous sulfate [23,28], microencapsulated ferrous fumarate [24], unknown iron source [25][26][27], ferrous sulfate monohydrate chelated with malic acid and sodium hexametaphosphate [29], ferrous sulfate hydrate encapsulated with partially hydrogenated vegetable oil [32], chelated ferrous sulfate [34][35][36][37], H-reduced elemental iron encapsulated with partially hydrogenated vegetable oil [39], ferrous sulfate citrate [40], or NaFeEDTA [40][41][42][43]. Blood hemoglobin was the main hematological indicator in all studies to evaluate the effect of iron fortification.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…20 With respect to bioavailability measured by hemoglobin and other biochemical measures, encapsulation of iron resulted in adequate iron bioavailability, but also unacceptable organoleptic changes. [42][43][44][45] One of the few candidate fortificants of DFS was ferric pyrophosphate, but its use has been limited by inferior bioavailability. However, parallel work demonstrated that particle-size reduction of ferric pyrophosphate could enhance bioavailability.…”
Section: Bioavailability Of Iron In Dual-fortified Salt With Iodinementioning
confidence: 99%